Clinical evidence of parietal cortex dysfunction and correlation with extent of allodynia in CRPS type 1. (7th November 2012) - Cohen, H.; McCabe, C.; Harris, N.; Hall, J.; Lewis, J.; Blake, D.R.
Abstract Background Unusual symptoms such as digit misidentification and neglect‐like phenomena have been reported in complex regional pain syndrome (CRPS), which we hypothesized could be explained by parietal lobe dysfunction. Methods Twenty‐two patients with chronic CRPS attending an in‐patient rehabilitation programme underwent standard neurological examination followed by clinical assessment of parietal lobe function and detailed sensory testing. Results Fifteen (68%) patients had evidence of parietal lobe dysfunction. Six (27%) subjects failed six or more test categories and demonstrated new clinical signs consistent with their parietal testing impairments, which were impacting significantly on activities of daily living. A higher incidence was noted in subjects with >1 limb involvement, CRPS affecting the dominant side and in left‐handed subjects. Eighteen patients (82%) had mechanical allodynia covering 3–57.5% of the body surface area. Allochiria (unilateral tactile stimulation perceived only in the analogous location on the opposite limb), sensory extinction (concurrent bilateral tactile stimulation perceived only in one limb), referred sensations (unilateral tactile stimulation perceived concurrently in another discrete body area) and dysynchiria (unilateral non‐noxious tactile stimulation perceived bilaterally as noxious) were present in some patients. Greater extent of body surface allodynia was correlated with worse parietal function (Spearman's rho = −0.674, p = 0.001). Conclusion In patients with chronic CRPS, detailed clinical examination may reveal parietal dysfunction, with severity relating to the extent of allodynia.